In Vitro Studies on Therapeutic Effects of Cannabidiol in Neural Cells: Neurons, Glia, and Neural Stem Cells - Jungnam Kim; Hyunwoo Choi; Eunhye K. Kang; Gil Yong Ji; Youjeong Kim; Insung S. Choi (Molecules, 2021)
(‒)-Cannabidiol (CBD) is one of the major phytocannabinoids extracted from the Cannabis genus. Its non-psychoactiveness and therapeutic potential, partly along with some anecdotal—if not scientific or clinical—evidence on the prevention and treatment of neurological diseases, have led researchers to investigate the biochemical actions of CBD on neural cells. This review summarizes the previously reported mechanistic studies of the CBD actions on primary neural cells at the in vitro cell-culture level. The neural cells are classified into neurons, microglia, astrocytes, oligodendrocytes, and neural stem cells, and the CBD effects on each cell type are described. After brief introduction on CBD and in vitro studies of CBD actions on neural cells, the neuroprotective capability of CBD on primary neurons with the suggested operating actions is discussed, followed by the reported CBD actions on glia and the CBD-induced regeneration from neural stem cells. A summary section gives a general overview of the biochemical actions of CBD on neural cells, with a future perspective. This review will provide a basic and fundamental, but crucial, insight on the mechanistic understanding of CBD actions on neural cells in the brain, at the molecular level, and the therapeutic potential of CBD in the prevention and treatment of neurological diseases, although to date, there seem to have been relatively limited research activities and reports on the cell culture-level, in vitro studies of CBD effects on primary neural cells.